From ITS to C-ITS highway roadside infrastructure: the handicap of a headstart? - Thibault Degrande; Frederic Vannieuwenborg; Didier Colle; Sofie Verbrugge (International Telecommunications Society (ITS), 2021)
To date, traffic remains a major source of societal costs in terms of safety and environment. In Flanders, as in other regions and Member States in the European Union, the government counts on current developments in cooperative, connected and autonomous mobility (CCAM) to achieve European societal objectives. However, the first set of Cooperative Intelligent Transport Systems (C-ITS) services has overlapping objectives with the functionalities of present ITS infrastructure. Therefore, this paper provides a methodology for road authorities to determine, bottom-up, the incremental benefits C-ITS can bring for the highway segments they operate, given the presence of ITS gantries on those segments. This allows to prioritize segments for C-ITS roadside unit (RSU) deployments, taking into account legacy ITS infrastructure. Results show that segments with dense ITS deployments, though having high traffic volumes, should not be prioritized in RSU deployment selection.
Keywords: 330